The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.pan.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased tissue and circulating levels of dipeptidyl peptidase-IV enzymatic activity in patients with pancreatic ductal adenocarcinoma

Abstract: DPP-IV-like enzymatic activity is upregulated in PDAC tissues. PDAC patients with recent onset diabetes or prediabetes have increased plasmatic DPP-IV enzymatic activity. These changes may contribute to the frequently observed association of PDAC and recent onset impairment of glucoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
1
18
1
Order By: Relevance
“…FAP immunopositivity was detectable by WB in most of the high-grade glioma samples, but was absent in the DPP-IV negative gliomas. This is consistent with ours as well as other authors' reports suggesting the coexpression and possible coregulation of DPP-IV and FAP in glioma cells and tissues 11,31 , human pancreatic alpha cells 37 and in some cancer cell lines 38 . The coexpression of DPP-IV and FAP was also described in endothelial cells, where both molecules are part of proteolytically active heteromeric aggregates with a molecular weight of 820 kDa, promoting cell migration and invasion 30 .…”
supporting
confidence: 94%
“…FAP immunopositivity was detectable by WB in most of the high-grade glioma samples, but was absent in the DPP-IV negative gliomas. This is consistent with ours as well as other authors' reports suggesting the coexpression and possible coregulation of DPP-IV and FAP in glioma cells and tissues 11,31 , human pancreatic alpha cells 37 and in some cancer cell lines 38 . The coexpression of DPP-IV and FAP was also described in endothelial cells, where both molecules are part of proteolytically active heteromeric aggregates with a molecular weight of 820 kDa, promoting cell migration and invasion 30 .…”
supporting
confidence: 94%
“…In human tumor-adjacent tissues, FAP was detectable at the RNA level by RT-PCR in the context of esophageal squamous cell carcinoma (ESCC)( 19 ), lung carcinoma( 18 ), and glioma( 17 ). At the protein level, FAP was found in pancreatic ductal adenocarcinoma (PDAC) adjacent tissue( 20 , 21 ). However, data obtained from non-tumor-bearing subjects suggest that some of these instances of tumor-adjacent FAP expression are not reflective of FAP expression in healthy tissues.…”
Section: Patterns Of Fap Expression In Cancermentioning
confidence: 99%
“…In the pancreas, single cell RNA sequencing revealed that FAP expression is specific to alpha-cells within normal islets( 24 ). Though the cellular source is unknown, FAP can also be detected in the plasma of healthy donors( 20 , 25 ). These data suggest that, while FAP up-regulation in tumors does provide a potential therapeutic window, its expression in healthy tissues may not be as restricted as previously thought, and must be taken into consideration when evaluating the potential side effects of targeting FAP.…”
Section: Patterns Of Fap Expression In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating FAPα levels were demonstrated significantly lower in cancer patients compared with healthy subjects and correlated inversely with survival in most types of cancer [69]. However, the circulating FAPα level in ESCC is still unclear.…”
Section: Introductionmentioning
confidence: 99%